Aktivitas Antibakteri Ekstrak Cacing Laor Hasil Ekstraksi Dengan Pelarut Berbeda Terhadap Bakteri Escherichia Coli - Abdul M Ukratalo; Mas’uth Pratomo MS; Zulhaimi Hendrajid (Jurnal Multidisiplin Madani, 2022)
Laor worms (Lysidice oela) are worms that appear on the surface of the Maluku sea to reproduce in March or April. Laor worms are usually consumed by the most people because they contain 13.92% protein, 81.51% water, 1.01% fat, and 2.41% ash and contain 9 types of essential amino acids. Secondary metabolite compounds (bromophenol) from marine worms are antimicrobial. The purpose of this research was to determine the potential of secondary metabolites in inhibiting the growth of E. coli bacteria. Laor worm is extracted maceration with ethanol, ethyl acetate and petroleum ether. The results of each extract were tested for antibacterial activity using the disc diffusion method with variations in concentrations of 25, 50, 75, 100 and 125 mg/mL against E. coli bacteria. The results showed that laor worm extract could inhibit the growth of E. coli bacteria with an inhibition zone area of 13.4 mm for ethanol extract; 14.8 for ethyl acetate extract and 12.6 mm for petroleum ether extract